2018
DOI: 10.1584/jpestics.d18-036
|View full text |Cite
|
Sign up to set email alerts
|

イネの酢酸処理に伴うgaba生合成とその蓄積

Abstract: Rice seedlings (Oryza sativa) that have died from drought cannot be rescued by watering afterward, but pre-treatment with exogenous acetic acid enabled the plants to produce shoots again after being watered (hereinafter referred to as "drought resilience"). To elucidate the metabolism of acetic acid, we treated rice plants with 13 C-labeled acetic acid and traced 13 C-labeled metabolites using LC-MS and 13 C-NMR techniques. The LC-MS and 13 C-NMR spectral data of the root extracts indicated that the acetic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, with the deepening of drought, plant root respiration is reduced, resulting in an insufficient supply of ATP (adenosine triphosphate) and a significant decrease in root activity that leads to slowing or even stops the growth ( Kim, Chae & Choi, 2020 ; Nikolova et al, 2020 ). The water balance in plants also alters, causing irreversible damage to the plants ( Ma et al, 2012 ; Isaji et al, 2018 ). Some studies found that under short-term drought stress, Robinia pseudoacacia absorbs more water by promoting the relative growth of fine roots.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the deepening of drought, plant root respiration is reduced, resulting in an insufficient supply of ATP (adenosine triphosphate) and a significant decrease in root activity that leads to slowing or even stops the growth ( Kim, Chae & Choi, 2020 ; Nikolova et al, 2020 ). The water balance in plants also alters, causing irreversible damage to the plants ( Ma et al, 2012 ; Isaji et al, 2018 ). Some studies found that under short-term drought stress, Robinia pseudoacacia absorbs more water by promoting the relative growth of fine roots.…”
Section: Introductionmentioning
confidence: 99%
“…1) suggest that acetic acid-induced signals in roots are transported to shoots. We have recently shown that the exogenously applied acetic acid to rice seedlings is converted to γ-amino butyric acid (GABA) in roots 18 , and therefore we examined here whether GABA and/or other metabolites are transported from roots to shoots in rice. Methyl- 13 C-labeled acetic acid was applied to 2-week-old rice seedlings and xylem sap of the treated seedlings was collected and analyzed by 13 C-NMR ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High pH protection of high acetic acid concentrations is not complete, suggesting additional detrimental factors are at play under these conditions. This root growth sensitivity complicates interpretation of the recently reported water stress related phenotypes induced by acetic acid (Kim et al, 2017;Isaji et al, 2018;Rahman et al, 2019;Utsumi et al, 2019), where [HAc] was undefined. The presence of low concentrations of residual ethanol in the treatment vinegar has the potential to confound these acetic acid effects.…”
Section: Discussionmentioning
confidence: 99%